Biological and Social Determinants of Fertility Behaviour among the Jat Women of Haryana State, India. (20th November 2016) - Chandiok, Ketaki; Mondal, Prakash Ranjan; Mahajan, Chakraverti; Saraswathy, Kallur Nava
Abstract : Fertility is a way through which human beings biologically replace themselves in order to continue their existence on earth. The present paper therefore attempts to study the factors affecting fertility among the Jat women of Haryana state. A household survey was conducted in 15 villages of Palwal district in which the concentration of Jats was found to be highest and 1014 ever married women were interviewed. Age at marriage, present age, education status, family type, and preference for male child were the most important factors that affected fertility in the studied population. Age at menarche, age at first conception, occupation status, use of birth control measures, and household per capita annual income did not affect the fertility in the studied population.